Dynamically upregulated mast cell CPA3 patterns in chronic obstructive pulmonary disease and idiopathic pulmonary fibrosis - Siddhuraj, Premkumar; Jönsson, Jimmie; Alyamani, Manar; Prabhala, Pavan; Magnusson, Mattias; Lindstedt, Sandra; Erjefält, Jonas S. (Frontiers in Immunology, 2022)
Background: The mast cell-specific metalloprotease CPA3 has been given important roles in lung tissue homeostasis and disease pathogenesis. However, the dynamics and spatial distribution of mast cell CPA3 expression in lung diseases remains unknown. Methods: Using a histology-based approach for quantitative spatial decoding of mRNA and protein single cell, this study investigates the dynamics of CPA3 expression across mast cells residing in lungs from control subjects and patients with severe chronic obstructive pulmonary disease (COPD) or idiopathic lung fibrosis (IPF). Results: Mast cells in COPD lungs had anatomically widespread increase of CPA3 mRNA (bronchioles p<0.001, pulmonary vessels p< 0.01, alveolar parenchyma p< 0.01) compared to controls, while granule stored CPA3 protein was unaltered. IPF lungs had a significant upregulation of both mast cell density, CPA3 mRNA (p<0.001) and protein (p<0.05) in the fibrotic alveolar tissue. Spatial expression maps revealed altered mast cell mRNA/protein quotients in lung areas subjected to disease-relevant histopathological alterations. Elevated CPA3 mRNA also correlated to lung tissue eosinophils, CD3 T cells, and declined lung function. Single cell RNA sequencing of bronchial mast cells confirmed CPA3 as a top expressed gene with potential links to both inflammatory and protective markers. Conclusion: This study shows that lung tissue mast cell populations in COPD and IPF lungs have spatially complex and markedly up-regulated CPA3 expression profiles that correlate with immunopathological alterations and lung function. Given the proposed roles of CPA3 in tissue homeostasis, remodeling and inflammation, these alterations are likely to have clinical consequences.